Methimazole-Induced Agranulocytosis - Bharathi, Tellagorla; Manikanta, Siram Teja; Raju, Viswanadhapalli Jaswanth; Pradeepthi, Katragadda; Vijayakumar, Ghanta; Kumar, Ghanta Vijaya (Indian Journal of Pharmacy Practice)
The antithyroid drug methimazole is used to treat patients with hyperthyroidism. Agranulocytosis is a rare and life-threatening adverse effect of the drug, characterized by a reduced circulating white blood cell count, which increases the risk of infections. We present the case of a 49-year-old male patient with a known history of hyperthyroidism for 10 years who was on tablet methimazole 10 mg three times daily. He presented with complaints of high-grade fever associated with chills for 2 days, sweating, body myalgias, difficulty in speaking due to neck swelling and palpitations. Laboratory investigations revealed severe neutropenia along with a thyrotoxic crisis. The patient's symptoms and laboratory abnormalities resolved after withdrawal of the drug, and he was managed with broad-spectrum antibiotics, propranolol, hydrocortisone, and cholestyramine. His neutrophil count normalized within 1 week. This case report highlights the importance of early identification of methimazole-induced agranulocytosis. Clinicians should maintain a high index of suspicion for rare life-threatening complications, of antithyroid drugs in patients presenting with infectious symptoms. Management of methimazole -induced agranulocytosis mainly involves discontinuation of the drug for preventing mortality associated with ATD-induced agranulocytosis.
Keywords: Agranulocytosis; Methimazole; Hyperthyroidism; Thyrotoxic crisis